Manga in America transnational book publishing and the domestication of Japanese comics - Brienza, Casey (Bloomsbury Academic, 2016)
"In Manga in America - the first ever book-length study of the history, structure, and practices of the American manga publishing industry - Casey Brienza explodes this assumption. Drawing on extensive field research and interviews with industry insiders about licensing deals, processes of translation, adaptation, and marketing, new digital publishing and distribution models, and more, Brienza shows that the transnational production of culture is an active, labor-intensive and oft-contested process of 'domestication.' Ultimately, Manga in America argues that the domestication of manga reinforces the very same imbalances of national power that might otherwise seem to have been transformed by it and that the success of Japanese manga in the United States actually serves to make manga everywhere more American." -- Back of book.